2022
DOI: 10.1109/access.2022.3204036
|View full text |Cite
|
Sign up to set email alerts
|

GCN-GAN: Integrating Graph Convolutional Network and Generative Adversarial Network for Traffic Flow Prediction

Abstract: As a necessary component in intelligent transportation systems (ITS), traffic flow-based prediction can accurately estimate the traffic flow in a certain period and area in the future. However, despite the success of traditional research and current machine learning methods, traffic flow prediction models have limitations in terms of prediction accuracy and efficiency. In this work, we propose a novel traffic flow prediction model named Graph Convolution and Generative Adversative Neural Network (GCN-GAN), whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…The methods of using artificial neural network models to predict short-term traffic flow [6] all have the problem of low prediction accuracy. The urban highway flow prediction model that integrates graph convolutional neural networks and generative adaptive neural networks (GCN-GAN) has weak interpretability [7]. The traffic flow prediction model that integrates LSTM and GCN can only achieve short-term prediction [8].…”
Section: Figure 1 Statistics Of Motor Vehicle Ownership In Chinamentioning
confidence: 99%
“…The methods of using artificial neural network models to predict short-term traffic flow [6] all have the problem of low prediction accuracy. The urban highway flow prediction model that integrates graph convolutional neural networks and generative adaptive neural networks (GCN-GAN) has weak interpretability [7]. The traffic flow prediction model that integrates LSTM and GCN can only achieve short-term prediction [8].…”
Section: Figure 1 Statistics Of Motor Vehicle Ownership In Chinamentioning
confidence: 99%
“…Wang et al [34] suggested a model that utilized GRU to produce aggregated spatial-temporal representations. Several models have employed multiple layers of RNN [16], [21], [33], [35], whereas others have used the attention mechanism [27], [28], [36], [37] to capture the long-term relationship in traffic data.…”
Section: A Temporal Feature Extractionmentioning
confidence: 99%
“…As transportation networks are inherently equipped with graph structures, the GNNs have become the most popular spatial feature extraction method for traffic forecasting. Convolutional GNNs have pioneered GNN-based traffic forecasting research, and have been widely used in concurrent models [15]- [17], [22], [28], [29], [31]- [33], [35], [37], [40], [43], [44], [47], [55]- [60], [62]- [64], [67], [71], [75], [95].…”
Section: B Spatial Feature Extraction With Graph Neural Networkmentioning
confidence: 99%
“…GCN excels at extracting structural features from graphs. Zheng et al [21] used GCN to predict traffic flow with the support of historical traffic flow datasets. This method can accurately estimate the future traffic flow for specific time periods and regions.…”
Section: Introductionmentioning
confidence: 99%